PERANCANGAN USER INTERFACE (UI) DAN USER EXPERIENCE (UX) UNTUK MENINGKATKAN AKSESIBILITAS DAN PENGEMBANGAN UMKM DI SOLO RAYA - Risma Meike Eko Wati; Sri Siswanti (Jurnal Ilmiah Informatika Komputer, 2025)
Rumah BUMN Solo is a center for empowering MSMEs that focuses on developing business actors through training and digital product promotion. However, the management of information and digital services is still not optimal. overcome this problem. The aim of this research is to design the Rumah BUMN Solo website and mobile site for MSMEs in Greater Solo by identifying user needs using a design thinking approach and finding solutions by designing an effective user interface (UI) and user experience (UX). The design thinking approach is applied through five stages: empathize, define, ideate, prototype, and test in order to explore problems and understand users and produce creative solutions. The research results are a UI/UX-based website. prototype designed to make it easier for MSMEs to access services such as training registration, uploading products, downloading certificates, and booking working space. Evaluation was carried out using the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) methods. Testing results show a good level of usability with an SUS score of 75 for administrators and 82.9 for MSMEs. Apart from that, all aspects of UEQ are considered to be in the excellent category, based on the evaluations given by respondents.